Ciliary membrane proteins traffic through the Golgi via a Rabep1/GGA1/Arl3-dependent mechanism - Kim, Hyunho; Xu, Hangxue; Yao, Qin; Li, Weizhe; Huang, Qiong; Outeda, Patricia; Cebotaru, Valeriu; Chiaravalli, Marco; Boletta, Alessandra; Piontek, Klaus; Germino, Gregory G.; Weinman, Edward J.; et al. (Nature, 2014)
Primary cilia contain specific receptors and channel proteins that sense the extracellular milieu. Defective ciliary function causes ciliopathies such as autosomal dominant polycystic kidney disease (ADPKD). However, little is known about how large ciliary transmembrane proteins traffic to the cilia. Polycystin-1 (PC1) and -2 (PC2), the two ADPKD gene products, are large transmembrane proteins that co-localize to cilia where they act to control proper tubular diameter. Here we describe that PC1 and PC2 must interact and form a complex to reach the trans-Golgi network (TGN) for subsequent ciliary targeting. PC1 must also be proteolytically cleaved at a GPS site for this to occur. Using yeast two-hybrid screening coupled with a candidate approach, we identify a Rabep1/GGA1/Arl3-dependent ciliary targeting mechanism, whereby Rabep1 couples the polycystin complex to a GGA1/Arl3-based ciliary trafficking module at the TGN. This study provides novel insights into the ciliary trafficking mechanism of membrane proteins.
Keywords: Membrane trafficking; Golgi; Membrane proteins; UMBC High Performance Computing Facility (HPCF)